Development of a versatile multi-material gripper - Goh, Daniel Jee Seng (Nanyang Technological University, 2024)
Traditionally rigid grippers stemming from conventional manufacturing methods excel in precise force and position control, however, lacking ability for wider range of object geometries without the need for multiple specialised designs. Soft grippers, which development was accelerated by the advent of accessible consumer additive manufacturing solutions, excel in compliance and conformability to a wide range of object geometries and surfaces but lack precise force and position control without more complex design strategies. This report presents the development of a versatile multi-material gripper, intended to attain the advantages of both conventionally rigid grippers and soft grippers by selective joint tuning. The project builds on and enhances a previously conceptualised joule-heated variable stiffness finger by incorporation of four key design elements: a temperature feedback component, a control system for selective heating control and servo actuation, an active cooling element, and a self-restorative joint mechanism. The prototype was iteratively designed and integrated into a multi-configuration three-finger gripper with printed circuit board for enclosing electrical circuitry. The key elements were evaluated first by verification of thermocouple readings through comparison with thermal imaging, followed by tests for assessing capability to maintain various target temperatures for a period of 120 seconds. The active cooling channel performance was then determined through comparison with passive cooling time taken for temperature drop from various temperatures above glass transition of polylactic acid to a target of 30°C. The novel spring-back mechanism for self-restorative forces was then evaluated for ability to restore the gripper’s initial equilibrium form through 20 cycles of actuation. This project contributes to demonstrating application of build-on-demand additively manufactured grippers by developing a fabrication protocol for a gripper capable of achieving multiple gripper joint configurations by selective joint rigidity tuning, thereby also enabling the benefits of both soft and rigid grippers.